Pengaruh Literasi Keuangan, Financial Technology, Dan Gaya Hidup Hedonisme Terhadap Perilaku Pengelolaan Keuangan Pribadi Pada Generasi Z Di Kota Denpasar - Maharani, Putu Serly; Kusuma, Putu Sri Arta Jaya (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
This study examines how financial literacy, financial technology, and lifestyle hedonism impact the personal financial management behavior of generation Z in Denpasar. In the study, quantitative methods were used. The sample was created based on a survey given to generation Z in Denpasar. The study had 80 respondents. The sampling method used purposive sampling method. Furthermore, questionnaires were distributed and evaluated using a Likert Scale with values from 1 to 5 for each question. Data testing was also conducted using SPSS version 29, which includes instrument test, classical assumption test, and hypothesis testing. The findings of this study are expected to provide valuable insights into how financial literacy, financial technology, and hedonic lifestyle influence the personal financial management behavior of Generation Z in Denpasar. The results of this study indicate that financial literacy and financial technology have a major influence on financial management behavior. In addition, the hedonism lifestyle factor does not have a significant impact on how a person manages finances.